2022
DOI: 10.3390/rs14102378
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Shallow Network for River Ice Segmentation

Abstract: River ice segmentation, used for surface ice concentration estimation, is important for validating river processes and ice-formation models, predicting ice jam and flooding risks, and managing water supply and hydroelectric power generation. Furthermore, discriminating between anchor ice and frazil ice is an important factor in understanding sediment transport and release events. Modern deep learning techniques have proved to deliver promising results; however, they can show poor generalization ability and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…During the ice-pans floating period, the surface layer of flowing water lost too much heat due to the decrease in air temperature [19]. On the other side, the turbulent mixing process of flowing water causes the heat exchange between the water surface layer and the main water body.…”
Section: Of 18mentioning
confidence: 99%
“…During the ice-pans floating period, the surface layer of flowing water lost too much heat due to the decrease in air temperature [19]. On the other side, the turbulent mixing process of flowing water causes the heat exchange between the water surface layer and the main water body.…”
Section: Of 18mentioning
confidence: 99%
“…A study by Sobiech and Dierking [39] evaluated the performance of kmeans classification on lakes and river channels of the central Lena Delta and showed that it is comparable to that of a fixed-threshold approach. Neural networks, support vector machines (SVMs), and RF classifiers are popular examples of supervised learning methods used in river and lake ice classification [40][41][42]. A review study by Belgiu and Drăguţ [43] reports that RF classifiers outperform artificial neural network classifiers in terms of classification accuracy and provide slightly better results than SVMs for highdimensional input data such as hyperspectral imagery [43,44].…”
Section: Introductionmentioning
confidence: 99%